Emerging Trends in Money Scams Targeting Adult Telegram Users in Malaysia - Faharudin, Nur Syifaa’; Nabilah Othman, Nur Azyan; Nursabrina Badrulzaman, Sarah; Mohd Nazril, Alis; Jamri, Mohamad Hafifi; Suryana, Nanang; Djuyandi, Yusa (PT. Data Jaringan Visual Indonesia (Djava), 2025)
The rise of cyber fraud targeting Telegram users in Malaysia poses a major threat to the trust and financial security of the digital platform. Therefore, this study will focus on two main objectives, which are to identify the strategies used by scammers to target adult users of Telegram Malaysia and evaluate the effectiveness of public awareness efforts aimed at educating the public about scams among Telegram users. By using Uses and Gratification Theory, which states that individuals engage with media to fulfill social and psychological needs, this research explores why scammers exploit Telegram's large user base and secure messaging for financial gain. To ensure accurate and reliable findings, a quantitative methodology was employed, using a structured questionnaire distributed via Google Forms, gathering responses from 416 participants through the integration of purposive and convenience sampling, chosen for its efficiency in reaching a diverse respondent pool. The results show that users are aware of online scams and can identify their various patterns as well as prevalent tactics. Susceptibility can be caused by a variety of factors, including a lack of awareness, being easily deceived, and financial desperation. Hence, in order to prevent cybercrime and promote digital safety, it is crucial to put pre-emptive measures into place, collaborate with governments, and launch effective awareness programs. In conclusion, social media platforms serve as vital tools for disseminating scam-related information.